A Dynamic Stakeholders' Framework in a Marketing Systems Setting. (June 2019) - Domegan, Christine; McHugh, Patricia; Flaherty, Tina; Duane, Sinead
A marketing systems approach to stakeholders has never been more important in an increasingly interconnected world. Recognising the inherent limitations of a firm-centric stakeholder stance, this paper proposes a dynamic stakeholders framework to examine the interacting nature of interrelated and interdependent stakeholder effects from a societal perspective. It presents a systemic stakeholders framework that incorporates several defining features and core propositions based on Layton's MAS mechanisms and Coleman's Boat. The contribution of a dynamic stakeholders' marketing system framework is not so much in identifying or defining the appropriate marketing mechanisms at work but in understanding the continuous feedback nature of the macro-micro-macro everyday dynamics which stakeholders listen to, learn about and leverage to act, react and interact.